The association between neighborhood obesogenic factors and prostate cancer risk and mortality: the Southern Community Cohort Study - Kumsa, Fekede Asefa; Fowke, Jay H.; Hashtarkhani, Soheil; White, Brianna M.; Shrubsole, Martha J.; Shaban-Nejad, Arash (Frontiers in Oncology, 2024)
Background: Prostate cancer is one of the leading causes of cancer-related mortality among men in the United States. We examined the role of neighborhood obesogenic attributes on prostate cancer risk and mortality in the Southern Community Cohort Study (SCCS).From the total of 34,166 SCCS male participants, 28,356 were included in the analysis. We assessed the relationship between neighborhood obesogenic factors (neighborhood socioeconomic status (nSES), and neighborhood obesogenic environment indices including restaurant environments index, retail-food environment index, parks, recreational facilities, and businesses) and prostate cancer risk and mortality by controlling for individual level factors using a multivariable Cox proportional hazards models. We further stratified prostate cancer risk analysis by race and body mass index (BMI).Results: Median follow-up time was 133 months (IQR: 103, 152), and the mean age was 51.62 (SD±8.42) years. There were 1,524 (5.37%) prostate cancer diagnoses and 98 (6.43 %) prostate cancer deaths during follow-up. Compared to participants residing in the wealthiest quintile, those residing in the poorest quintile had a higher risk of prostate cancer (aHR=1.32, 95% CI 1.12-1.57, p=0.001), particularly among non-obese men with a BMI<30 (aHR=1.46, 95% CI 1.07-1.98, p=0.016). The restaurant environment index was associated with a higher prostate cancer risk in overweight (BMI≥25) White men (aHR = 3.37, 95% CI 1.04-10.94, p=0.043, quintile 1 vs None). Obese Black individuals without any neighborhood recreational facilities had a 42% higher risk (aHR=1.42, 95% CI 1.04-1.94, p=0.026) compared to those with any access. Compared to residents in the wealthiest quintile and most walkable area, those residing within the poorest quintile (aHR=3.43, p=0.003) or the least walkable area (aHR=3.45, 95%CI 1.22-9.78, p=0.020) had a higher risk of prostate cancer death.Living in a lower-nSES was associated with a higher prostate cancer risk, particularly among Black men. Restaurant and retail-food environment indices were also associated with a higher prostate cancer risk, with stronger associations within overweight White individuals. Finally, residing in a low SES neighborhood or the least walkable areas were associated with a higher risk of prostate cancer mortality.